On Writing Notes in the Field: Interrogating positionality, emotion, participation and ethics - Thompson, Jennifer (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2014)
Fieldnotes help researchers document research activities and position themselves in the field, invariably constructing the research, the researcher and the knowledges produced. Yet the process of how fieldnotes are produced often remains invisible. These “Notes from the Field” explore one doctoral student’s experiences writing fieldnotes. Interrogated here are some of the tensions that emerged writing fieldnotes in relation to positionality and emotion, as well as regarding participation and ethics.